Genome-Wide Identification and Expression Analysis of the KUP Family under Abiotic Stress in Cassava (Manihot esculenta Crantz) - Ou, Wenjun; Mao, Xiang; Huang, Chao; Tie, Weiwei; Yan, Yan; Ding, Zehong; Wu, Chunlai; Xia, Zhiqiang; Wang, Wenquan; Zhou, Shiyi; Li, Kaimian; Hu, Wei (Frontiers in Physiology, 2018)
KT/HAK/KUP (KUP) family is responsible for potassium ion (K+) transport, which plays a vital role in the response of plants to abiotic stress by maintaining osmotic balance. However, our understanding of the functions of the KUP family in the drought-resistant crop cassava (Manihot esculenta Crantz) is limited. In the present study, 21 cassava KUP genes (MeKUPs) were identified and classified into four clusters based on phylogenetic relationships, conserved motifs, and gene structure analyses. Transcriptome analysis revealed the expression diversity of cassava KUPs in various tissues of three genotypes. Comparative transcriptome analysis showed that the activation of MeKUP genes by drought was more in roots than that in leaves of Arg7 and W14 genotypes, whereas less in roots than that in leaves of SC124 variety. These findings indicate that different cassava genotypes utilize various drought resistance mechanism mediated by KUP genes. Specific KUP genes showed broad upregulation after exposure to salt, osmotic, cold, H2O2, and abscisic acid (ABA) treatments. Taken together, this study provides insights into the KUP-mediated drought response of cassava at transcription levels and identifies candidate genes that may be utilized in improving crop tolerance to abiotic stress.